Risk assessment of Bundeswehr (German Federal Armed Forces) permethrin-impregnated battle dress uniforms (BDU) - Appel, Klaus E.; Gundert-Remy, Ursula; Fischer, Horst; Faulde, Michael; Mross, Klaus G.; Letzel, Stephan; Rossbach, Bernd (International journal of hygiene and environmental health, 2008)
In an age when vector-borne diseases are emerging worldwide, personal protective measures are essential for shielding soldiers and other exposed persons from arthropod attack. The development of permethrin-impregnated clothing has been one recent advance in protecting persons at-risk. However, to date risk assessment has not been performed related to wearing permethrin-impregnated clothing over longer time periods. Therefore, this paper describes relevant toxicological aspects of permethrin and estimates the extent of dermal permethrin uptake by soldiers wearing impregnated uniforms by determining urine metabolites of permethrin. The exposure monitoring conducted in wearers of untreated uniforms did not show any signs of increased permethrin uptake and was similar to that of the general population in Germany. By contrast, studies involving the soldiers wearing permethrin- impregnated uniforms identified far higher internal exposure, the amounts of urine metabolites clearly above the reference value for the background exposure of the German population at large. Comparing the median excretion values, an approximately 200 times higher exposure can be assumed. The excretion levels of the subject with the maximum amount of metabolites correspond to an internal exposure of around 5–6 μg/kg body weight and day thereby considering that biomonitoring could not take all urine metabolites and other elimination routes into account. Based on an oral absorption rate of 50%, the internal dose of 5–6 μg/kg body weight and day would correspond to an oral uptake of permethrin which is around 20% of the ADI value of 50 μg/kg body weight and day. In addition, based on these data and using a dermal absorption rate of 2% the permethrin dose reaching the skin was estimated to be 250 μg/kg body weight and day. Considering a standard body weight and the area covered by the uniform, an exposure level of about 1.25 μg permethrin/cm 2 skin and day can be calculated. Clinical subjective symptoms were recorded by means of a self-reporting questionnaire which has been developed and used for this specific purpose in environmental outpatient departments in both groups (wearers of impregnated versus non-impregnated uniforms). Only minor sensory impairments were identified in one of the studies (Kabul/Afghanistan) which may represent skin paraesthesiae. Based on these results, it can be assumed that the normal use of permethrin-treated uniforms does not affect human health to a clinical relevant extent. We recommend that the release rate of permethrin from the textile material should be strictly monitored by means of a quality assurance method. It should comply with standards to which the results of this study may contribute.